Design of a Tri-Band CubeSat RF Payload System for High Resolution Ionospheric Parameter Measurement - Lanter, Ferry Pascal (Curtin University, 2024)
Current and next generation low frequency radio telescopes require external ionospheric measurement data for some calibrations that is an order of magnitude higher in resolution than the currently available data from Global Navigational Satellite System Signals. This thesis presents the design of a 3U CubeSat radio frequency payload system that enables a cost feasible ionospheric remote sensing solution for addressing current and future low frequency radio astronomy calibration challenges using a small satellite.